Boosting Residential Property Sales with Integrated Marketing Communication Strategies - Kristanto, Harys; Arumdini, Savira; Fardhon, Muhammad (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2025)
The increasing demand for suburban housing in Indonesia, driven by urban expansion and rising middle-class aspirations, has intensified competition among real estate developers. This study investigates how Integrated Marketing Communication (IMC) strategies influence consumer interest in purchasing residential property in Bekasi Regency, a fast-growing suburban area. Using a qualitative design, data were collected through in-depth interviews and focus group discussions involving marketing professionals, developers, and prospective buyers at PT Refaro Central Propertindo. The analysis integrates the Theory of Planned Behavior (TPB) and the AIDA (Attention, Interest, Desire, Action) model to explore both psychological drivers and communication dynamics. Findings reveal that consistent messaging, immersive digital tools (e.g., virtual tours, AI chatbots), and personalized engagement significantly affect buyer attitudes, social norms, and perceived control ultimately enhancing purchase intention. The application of AIDA further explains how IMC guides consumers through each stage of the decision-making process. This study offers a novel contribution by combining TPB and AIDA in a real estate context, providing deeper insights into consumer behavior and communication strategy effectiveness. Practically, the research recommends hybrid IMC approaches that integrate digital innovation with trust-building offline experiences. These findings are particularly relevant for developers targeting suburban markets in Indonesia and other emerging economies.